The Reconstruction of Village Governance Towards Good Governance (Study in Kalianda District, South Lampung Regency) - Erina Pane (Fiat Justisia: Jurnal Ilmu Hukum, 2019)
The reconstruction of village governance begins with the promulgation of the village law to protect and empower villages to become strong, advanced, independent and democratic. This paradigmatic law to bring the changes to village governance at the regional government level. The construction of the autonomy of the village law places village arrangements as part of the concept of decentralisation and village autonomy. These changes have implications for the shift in position, extent of authority, power relations and implementation of financial policies between villages and local governments. This study used a normative-empirical approach. The results of the study showed that the implementation of the reconstruction of village governance requires a unified understanding of village government officials, village community organisations, community leaders and religious leaders regarding the principles of participation, transparency, and accountability to increase community enthusiasm, motivation and creativity in village development.